Penerapan Algoritma K-Means Tingkat Kesehatan Bayi (Studi Kasus :Dinas Kesehatan Kota Binjai) - Roma Uli Br Sitanggang (Department of Information Technology, Universitas Timor, Indonesia, 2022)
The Binjai City Health Office always conducts counseling and weighing for babies and provides information to parents about nutrition and health for babies and provides information to parents about nutrition and health in children so they are not susceptible to disease. Due to limited knowledge of parents about health and nutrition In infants, it is very worried about children who are malnourished and cause children to be easily infected with viruses and diseases, both minor and dangerous diseases. Cluster analysis is the work of classifying data (objects) based only on the information found in the data that describes these objects and the relationships between them. Objects that are joined in a group are objects that are similar (or related) to each other and different (not related) to objects in other groups. One of the most widely used methods in the cluster method is the K-Means algorithm. From the tests carried out using the clustering method with the k-means algorithm, cluster 2 of the criteria for age, body weight, body length, and motor ability, the group that has the highest and most set / value, namely in Cluster 2 totals 624 data on infant health levels. and in cluster 2 in the group of babies aged 4-6 months and weighing 4-8 kg and 55-63.5 cm long and having the ability to crawl, try to stand with assistance. And it can be seen that the 3 clusters of the criteria for Age, Weight, Body Length, and Motoric ability, the group that has the highest and most sets / values, namely in Cluster 2 totaling 368 data on the health level of infants and in cluster 2 in the group of infants aged 4-6 months. and has a body weight of 4-8 kg and a display body of 55-63.5 cm and has the ability to crawl, materials to try to stand up with assistance. And it can be seen that the 3 clusters of the criteria for age, weight, body length, and motor ability, the group that has the highest and most sets / values, namely in Cluster 4 totaling 348 data on infant health levels and in cluster 4 in the group of infants aged 7-9 months and has a body weight of 4-8 kg and a body length of 55-63.5 cm and has the ability to crawl, move the buttocks, roll, or a combination of various movements.